2017
DOI: 10.1038/ncomms14008
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of annual temperature cycle over the Tibetan Plateau since the 1870s

Abstract: The annual cycle of extra-tropical surface air temperature is an important component of the Earth's climate system. Over the past decades, a reduced amplitude of this mode has been observed in some regions. Although attributed to anthropogenic forcing, it remains unclear when dampening of the annual cycle started. Here we use a residual series of tree-ring width and maximum latewood density from the Tibetan Plateau >4,000 m asl to reconstruct changes in temperature seasonality over the past three centuries. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…The response functions analysis shows that despite significant responses of the MXD chronology with monthly temperature in the previous December, current August and September, as well as monthly precipitation in the current March, the strongest response relationship occurs in August‐September temperature (Figure ). There is no a clear physiological explanation for the response relationships of MXD with temperature in the previous December and precipitation in the current March; meanwhile, many studies have found that the August‐September temperature is the crucial controlling factor for MXD growth, and an accepted physiological mechanism has been provided (Duan et al, ; Duan & Zhang, , ; Li et al, ; Wang et al, ). Therefore, the August‐September mean temperature derived from the 79‐stations average was chosen as the reconstruction target.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The response functions analysis shows that despite significant responses of the MXD chronology with monthly temperature in the previous December, current August and September, as well as monthly precipitation in the current March, the strongest response relationship occurs in August‐September temperature (Figure ). There is no a clear physiological explanation for the response relationships of MXD with temperature in the previous December and precipitation in the current March; meanwhile, many studies have found that the August‐September temperature is the crucial controlling factor for MXD growth, and an accepted physiological mechanism has been provided (Duan et al, ; Duan & Zhang, , ; Li et al, ; Wang et al, ). Therefore, the August‐September mean temperature derived from the 79‐stations average was chosen as the reconstruction target.…”
Section: Resultsmentioning
confidence: 99%
“…An annual‐resolved historical temperature reconstruction from the perspective of the whole TP is very essential to evaluate the recent TP warming. Tree‐ring maximum late‐wood density (MXD) forms in the late growing season and is sensitive to temperature conditions (Duan et al, ; Stine & Huybers, ), especially in the high latitudes and high‐altitude regions (Briffa et al, ; Bräuning & Mantwill, ; Duan et al, , 2014, ; Fan et al, ; Wang et al, ; Yin et al, ). A network of tree‐ring MXD could be a potential proxy to reveal temperature variability over the past centuries from the perspective of the whole TP.…”
Section: Introductionmentioning
confidence: 99%
“…The black cross indicates the nearest meteorological station (MEK) from the tree‐ring site in this study (2018). The “tree‐ring sites (2014)” and “tree‐ring sites (2017)” indicate the site of tree‐ring MXD data reported in our previous publications (Duan and Zhang, ; Duan et al ., ), and the “tree‐ring site (2018)” indicates the new MXD chronology established in this study [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Methodsmentioning
confidence: 99%
“…Although the maximum length of chronologies derived from tree‐ring isotopes is shorter than those derived from tree‐ring width on the TP, a few tree‐ring isotope chronologies longer than 600 years have been established (Holmes et al ., ; Griessinger et al ., , ). Along with tree‐ring width and isotopes, tree‐ring density also displays great potential in reconstructing historical climate on the TP, especially for late summer or growing season temperatures (Bräuning and Mantwill, ; Fan et al ., ; Duan et al ., , ; Wang et al ., ; Chen et al ., ; Xing et al ., ; Duan et al ., ; Yin et al ., ; Duan et al ., ; Li et al ., ; Li et al ., ). However, the chronology length of published tree‐ring density records is less than 600 years on the TP to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation